Secure Communication Using Remote Procedure Calls - Birrell, Andrew (ACM Transactions on Computer Systems, 1985)
Research on encryption-based secure communication protocols has reached a stage where it is feasible to construct end-to-end secure protocols. The design of such a protocol, built as part of a remote procedure call package, is described. The security abstraction presented to users of the package, the authentication mechanisms, and the protocol for encrypting and verifying remote calls are also described.